The Impact of Service Quality on Customer Satisfaction and Loyalty in Netflix - Alnazarul, Dicky; I Kadek Dwi Nuryana (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
Netflix is a subscription streaming platform that gives users access toiwatchiTVishowsiand movies throughiinternet connectedidevices. The purposeiof this study is to determine whether there is an influence of service quality onicustomer loyaltyifor the Netflix online streaming application and to make appropriate recommendations to the relevant agencies. Thisistudy uses an explanatoryimethodiwhich aimsito explain the relationship betweeni the variables studied and the influence between these variables. Thisistudy involves three independent variables, namely service quality, Price, and customer satisfaction, and one dependent variable, namely customer loyalty. Data collection was carried out through distributing questionnaires to Netflix application users in Surabaya and its surroundings. Theidata obtained was processed using validity test, reliability test, and hypothesis testing with the help of SPSS software. The analysis results show that all independent variables have a significant influence on customer loyalty. Among these variables, Price has the greatest influenceion customer loyalty, followed by service quality and customer satisfaction. This study has some limitations that require further study so that the level of elearning user satisfaction can be measured more accurately. Keywords: Netflix, Satisfaction, Loyalty, SPSS, Customer Services.